Impact Assessment of Solar Power Generation Uncertainty on Smart Grid Reliability and Carbon Neutrality - Khalkho, Anant Milan; Rapada, Bhargav; Majumder, Gourab; Cherukuri, Murthy; Mohanta, Dusmanta Kumar (Frontiers in Energy Research, 2022)
The global concerted effort towards achieving carbon neutrality has given impetus to the accelerated growth of renewable energy sources with government patronage. The smart grid has the mandate to integrate renewable energy sources adeptly towards meeting the vision of meeting carbon neutrality by 2050 by many countries. Solar energy generation has emerged as one of the most viable options due to the rapid stride of innovations in this domain as well as due to decreasing trend of cost of photovoltaic (PV) technology. However, the uncertain sunlight leading to uncertain solar energy generation with low-capacity factor has been a challenge to maintain the legacy reliability of the power system. Unlike a two-state model being used for analyzing conventional generators, a multi-state model has been proposed for incorporating the random variation of solar energy generation correlating with random irradiance. An innovative approach for formulating probabilistic modelling of solar is implemented to evaluate different reliability indices such as loss of load probability (LOLP), expected energy not served (EENS). Different case studies with results prove the efficacy of the proposed probabilistic model-based availability of solar power generation due to solar irradiance uncertainty along with interaction with stochastic load model on Smart grid reliability and carbon neutrality.